2018
DOI: 10.1148/radiol.2018171657
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lesion Characterization with Spectral CT: Determining the Optimal Energy for Virtual Monoenergetic Reconstruction

Abstract: Purpose To investigate the relationship between energy level of virtual monoenergetic (VM) imaging and sensitivity in the detection of minimally enhancing renal lesions. Materials and Methods Phantoms simulating unenhanced and contrast material-enhanced renal parenchyma were equipped with inserts containing different concentrations of iodine (range, 0-1.15 mg iodine per milliliter). A total of 180 patients (117 men; mean age, 65.2 years ± 13.0 [standard deviation]) with 194 (62 solid, 132 cystic) renal lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Our findings showed that 40 keV VMI (+) provided the optimal visualization of NPC T1 and BH, and combined image features with quantitative parameters yielded the best performance for differentiating the 2 entities, with an AUC of 0.963, a sensitivity of 89.4%, and a specificity of 93.2%. DECT could yield VMIs at low-energy levels, increasing image contrast and reducing artifacts, enabling improvement of tumor discrimination (25)(26)(27). In our study, 40 keV VMI (+) in the contrast-enhanced phase yielded the highest subjective image quality scores, SNR and CNR, to detect NPC T1 .…”
Section: Discussionmentioning
confidence: 52%
“…Our findings showed that 40 keV VMI (+) provided the optimal visualization of NPC T1 and BH, and combined image features with quantitative parameters yielded the best performance for differentiating the 2 entities, with an AUC of 0.963, a sensitivity of 89.4%, and a specificity of 93.2%. DECT could yield VMIs at low-energy levels, increasing image contrast and reducing artifacts, enabling improvement of tumor discrimination (25)(26)(27). In our study, 40 keV VMI (+) in the contrast-enhanced phase yielded the highest subjective image quality scores, SNR and CNR, to detect NPC T1 .…”
Section: Discussionmentioning
confidence: 52%
“…Two radiologists independently drew circular regions of interest (ROIs) at the maximum slice of the tumor with an average area of 97.27 mm 2 on 70 keV monochromatic images in the AP and VP. Previous studies have shown that 70 keV monochromatic images may provide an optimal trade-off between sensitivity and specificity for abdominal lesion analysis ( 14 ). ROIs were placed on solid areas to avoid vascular, necrotic, and cystic changes as much as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The original data were reconstructed into 1.25 mm virtual monochromatic image sets using the adaptive statistical iterative reconstruction (ASIR) algorithm at 40% strength. The corticomedullary phase images at 70 keV energy level 17 were imported into ITK-Snap v.3.4.0 software (An open source software for medical image segmentation, URL https://www. itksnap.…”
Section: Voi Delineation and Radiomics Features Calculationmentioning
confidence: 99%